Fecal Metabolites Were Altered, Identified as Biomarkers and Correlated With Disease Activity in Patients With Systemic Lupus Erythematosus in a GC-MS-Based Metabolomics Study - Yan, Ren; Jiang, Huiyong; Gu, Silan; Feng, Ninghan; Zhang, Nan; Lv, Longxian; Liu, Fengping (Frontiers in Immunology, 2020)
Gut metabolites are products of the crosstalk between microbes and their host and play an important role in the occurrence, development, diagnosis and treatment of autoimmune diseases. This work profiled the faecal metabolome of patients with systemic lupus erythematosus (SLE) using gas chromatography–mass spectrometry (GC-MS) and analysed the potential roles of metabolites in the diagnosis and development of SLE. Faecal sample from twenty-nine SLE patients without any other diseases and 30 healthy controls (HCs) were analysed by metabolomics profiling. All participants took no antibiotics in the month before sampling and clinical data collecting. The metabolome profiles of patients with SLE and HCs were significantly different. Thirty faecal metabolites, such as deoxycholic acid, erucamide, L-tryptophan and putrescine, were significantly enriched, while nine metabolites, such as glyceric acid, γ-tocopherol, (Z)-13-octadecenoic acid and 2,4-di-tert-butylphenol, were depleted in SLE patients versus HCs. The areas under the curve (AUCs) of L-valine, pyrimidine, erucamide and L-leucine during ROC analysis were 0.886, 0.833, 0.829 and 0.803, indicating their good diagnostic potential. Moreover, the combination of L-valine, erucamide and 2,4-di-tert-butylphenol gave an AUC of 0.959. SLE-altered metabolites were significantly located in twenty-eight pathways, such as ABC transporter (p = 3.40E-13) and aminoacyl-tRNA biosynthesis (p = 2.11E-12). Furthermore, SLE-altered faecal metabolites were closely correlated with SLE indicators, e.g., L-tryptophan was positively correlated with the SLEDAI-2K (p = 0.007). Our results suggest that the SLE faecal metabolome is closely associated with the occurrence and development of SLE and is of great diagnostic value.